Pengaruh Metode Hypnoteaching Terhadap Motivasi Belajar Siswa Asrama Al-Falah Pondok Pesantren Darul Ulum Peterongan Jombang - Muhtadi Muhtadi; Muhammad Sholekhudin (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2019)
This study aims to determine the effect of the Hypnoteaching Method on the Motivation of Al-Falah Dormitory Student Learning in Darul Ulum Peterongan Islamic Boarding School Jombang. This type of research is qualitative descriptive research, which emphasizes the strength of the data analysis and data sources available. These sources the author obtained from various books and other writings by relying on existing theoretical theories to be interpreted clearly and deeply to produce theses and anti-theses by using documentation data collection techniques, observation and interviews or interviews. While the data analysis techniques use qualitative descriptive analysis techniques, through the stages of data reduction, data presentation and conclusion drawing. The results of the study showed that the hypnoteching method was very influential to foster the motivation of students learning Al-Falah Dormitory Darul Ulum Peterongan Islamic Boarding School Jombang.